Evolutionary dynamics of satellite DNA in plant genomes - Ávila Robledillo, Laura (Jihočeská univerzita, 2021)
Satellite DNA (satDNA) belongs to the highly repetitive fraction of eukaryotic genomes. It is best characterized by the formation of long arrays of almost identical sequences that are tandemly repeated. These repeats are widely distributed in plant species where they can make up a substantial proportion of their genomes. Despite the long history of satDNA research, the classic methodology did not allow for its comprehensive characterization. Consequently, the fragmentary information gathered during the last 60 years does not answer the many questions surrounding the evolution of these elements. The development of new techniques in sequencing, together with the availability of new bioinformatics tools for analyzing different genome fractions, has presented an opportunity to advance studies of tandem repeats. This thesis describes the landscape characterization of satDNA in the genome of Fabeae species by exploring the diversity of satDNA within a genome, the association of these elements with functional centromeres, as well as their genome-wide organization. We employed new computational pipelines specifically designed for the analysis of tandem repeats from next generation sequencing data, and combined their results with molecular and cytogenetic methods to achieve comprehensive characterization of the satellite repeats.
Evolutionary dynamics of satellite DNA in plant genomes
Keywords: Satellite DNA; cytogenetics; centromere evolution; plant chromosomes; CENH3; ChIP-seq; fluorescence in situ hybridization; Next Generation Sequencing; nanopore sequencing; Fabeae; Satellite DNA; cytogenetics; centromere evolution; plant chromosomes; CENH3; ChIP-seq; fluorescence in situ hybridization; Next Generation Sequencing; nanopore sequencing; Fabeae